2007
DOI: 10.1038/sj.jcbfm.9600477
|View full text |Cite
|
Sign up to set email alerts
|

Spectacular Shrinking Deficit: Insights from Multimodal Magnetic Resonance Imaging after Embolic Middle Cerebral Artery Occlusion in Sprague—Dawley Rats

Abstract: Almost no data is available on the serial changes in the brain after spectacular shrinking deficit (SSD) that may help understand this relatively rare clinical phenomenon. Quantitative diffusion-(DWI), perfusion-(PWI), T 1 -(T1WI), T 2 -weighted (T2WI), and functional magnetic resonance imaging (fMRI) were performed before, during, and up to 7 days after embolic middle cerebral artery occlusion (eMCAO) in male Sprague-Dawley rats (n = 9). Region of interest (ROI) analysis was used to evaluate structural and fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 23 publications
1
14
0
Order By: Relevance
“…These previous clinical observations are supported by our results. Similar changes in ADC values have also been reported in animal models 10, 22 and subsequent follow-up imaging or pathological examination frequently confirms infarction in these regions. In addition, DWI reversal is not “all or none” phenomenon; regions of DWI reversal often subsequently develop subtle abnormalities on delayed T2 or FLAIR imaging.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…These previous clinical observations are supported by our results. Similar changes in ADC values have also been reported in animal models 10, 22 and subsequent follow-up imaging or pathological examination frequently confirms infarction in these regions. In addition, DWI reversal is not “all or none” phenomenon; regions of DWI reversal often subsequently develop subtle abnormalities on delayed T2 or FLAIR imaging.…”
Section: Discussionsupporting
confidence: 81%
“…Although it is clear that early DWI lesions are not equivalent to the ischemic core 20, 21 , clinical and laboratory 22 studies have demonstrated that despite early reperfusion, only very limited tissue salvage occurs in coregistered regions that harbored acute DWI lesions. Early DWI reversal may result from the transient rise in ADC values that occurs following reperfusion.…”
Section: Discussionmentioning
confidence: 99%
“…(i) rICA patency was monitored only during 24 h and at 4 time points: baseline (before surgery), 1 h, 4 h and 24 h after clot embolization. We chose 1 h since most cases of early recanalization or inadequate positioning of the clot have been reported to occur during the first hours following clot embolization (Henninger et al, 2007). The second time point, 4 h, was chosen as it frames with human data indicating that reperfusion is significantly beneficial on stroke volume up to 4 h -4 h 30 min after stroke onset (Lees et al, 2010).…”
Section: Limitationsmentioning
confidence: 99%
“…Cerebrospinal fluid, specified as voxels with T 2 values at least 4.5 standard deviations higher than mean normal contralateral values (from 65 control rats), was excluded in further analysis. Infarcted tissue was automatically identified as voxels with T 2 values at least 2 standard deviations higher than mean contralateral graymatter values on poststroke day 3 (Group I) or 7 (Groups II and III) (T 2 -based lesion sizes at day 3 after permanent MCAo or at day 7 after embolic stroke have been shown to correspond with infarction size on postmortem histologic sections 23,24 ). Acute perfusion abnormality was similarly identified on acute MTT values.…”
Section: Image Processingmentioning
confidence: 99%